Content and chemical composition of the essential oil of Lippia gracilis Schauer accessions in different drying times - Juliana Oliveira de Melo; Arie Fitzgerald Blank; Alisson Marcel Souza de Oliveira; Thiago Matos Andrade; Maria de Fátima Arrigoni-Blank; Péricles Barreto Alves (Bioscience Journal, 2019)
Lippia gracilis, popularly known in Brazil as ‘alecrim-de-tabuleiro’, is used for many purposes, especially as antimicrobial and antiseptic. The drying process of aromatic and medicinal plants aims to minimize the loss of active principles and slow their deterioration, which may greatly influence the yield and chemical composition of some species. The objective of this study was to evaluate the effect of drying times (0, 2, 4, and 8 days) on the content and chemical composition of the essential oil of L. gracilis accessions LGRA-106, LGRA-109, and LGRA-201. The leaves were dried at 40 oC, and essential oil was extracted by hydrodistillation. Chemical analysis was performed by GC/MS. The experiment was carried out in a completely randomized design with three replications. The accessions of L. gracilis LGRA-106, LGRA-109, and LGRA-201 presented higher essential oil at four days of drying time. The accession LGRA-201 showed the highest essential oil yields at four and eight days of drying, with mean values of 0.038 and 0.029 mL g-1, respectively. The drying time did not influence the contents of thymol, methyl-thymol, γ-terpinene, and carvacrol in the essential oils of L. gracilis, but affected the contents of β-caryophyllene, p-cymene, and carvacrol acetate. The essential oils of the three accessions analyzed in this study revealed different chemical profiles.